Microplankton size structure induced by a warm-core eddy in the western Bay of Bengal: Role of Trichodesmium abundance - Karnan Chinnadurai; Jyothibabu Retnamma; Arunpandi Nagarathinam; Pandiyarajan Rethinam Subramanian; Parthasarathi Singaram; Santhikrishnan Shoba (Oceanologia, 2021)
Mesoscale warm-core eddies are common in the Bay of Bengal (BoB), and this study in the western BoB during Pre-Southwest Monsoon (April 2015) presents how a prolonged warm-core core eddy could modify the microplankton biomass and size structure. To investigate this, field sampling and laboratory analyses were augmented with satellite data sets of sea surface temperature (SST), winds, mean sea level anomaly (MSLA), geostrophic currents and chlorophyll-a. High SST with positive MSLA (≥ 20 cm) and a clockwise circulation, represented the occurrence of a large warm-core eddy in the western BoB. Time series data evidenced that it was originated in the mid of March and persistent there till early June, which in turn caused a decrease in the surface nutrients and chlorophyll-a. The abundance and biomass of microplankton were negligible in the warm-core eddy region. FlowCAM data showed a significant decrease in the autotrophic microplankton parameters in the warm-core eddy (av. 13 ± 9 ind. L−1 and 0.1 ± 0.04 µgC L−1, respectively) as compared to the surrounding locations (av. 227 ± 143 ind. L−1 and 0.8 ± 0.5 µgC L−1, respectively). Low nutrients level in the warm core eddy region favoured high abundance of needle-shaped phytoplankton cells dominated by Trichodesmium cells. As a result, the size of micro-autotrophs in the warm-core eddy was larger (av. 91,760 ± 12,902 µm3 ind.−1) than its outside (av. 50,115 ± 21,578 µm3 ind.−1). This is a deviation from our belief that the oligotrophy decreases the phytoplankton size. We showed here that the above understanding might not be infallible in warm-core eddies in the northern Indian Ocean due to its inducing effect on the Trichodesmium abundance.